The Opening of Connexin 43 Hemichannels Alters Hippocampal Astrocyte Function and Neuronal Survival in Prenatally LPS-Exposed Adult Offspring - Chávez, Carolina E.; Oyarzún, Juan E.; Avendaño, Beatriz C.; Mellado, Luis A.; Inostroza, Carla A.; Alvear, Tanhia F.; Orellana, Juan A. (Frontiers in Cellular Neuroscience, 2019)
Clinical evidence has revealed that children born from mothers exposed to viral and bacterial pathogens during pregnancy are more likely to suffer various neurological disorders including schizophrenia, autism bipolar disorder, major depression, epilepsy, and cerebral palsy. Despite that most research has centered on the impact of prenatal inflammation in neurons and microglia, the potential modifications of astrocytes and neuron-astrocyte communication have received less scrutiny. Here, we evaluated whether prenatally LPS-exposed offspring display alterations in the opening of astrocyte hemichannels and pannexons in the hippocampus, together with changes in neuroinflammation, intracellular Ca2+ and nitric oxide (NO) signaling, gliotransmitter release, cell arborization, and neuronal survival. Ethidium uptake recordings revealed that prenatal LPS exposure enhances the opening of astrocyte Cx43 hemichannels and Panx1 channels in the hippocampus of adult offspring mice. This enhanced channel activity occurred by a mechanism involving a microglia-dependent production of IL-1β/TNF-α and the stimulation of p38 MAP kinase/iNOS/[Ca2+]i-mediated signaling and purinergic/glutamatergic pathways. Noteworthy, the activity of Cx43 hemichannels affected the release of glutamate, [Ca2+]i handling, and morphology of astrocytes, whereas also disturbed neuronal function, including the dendritic arbor and spine density, as well as survival. We speculate that excitotoxic levels of glutamate triggered by the activation of Cx43 hemichannels may contribute to hippocampal neurotoxicity and damage in prenatally LPS-exposed offspring. Therefore, the understanding of how astrocyte-neuron crosstalk is an auspicious avenue towards the development of broad treatments for several neurological disorders observed in children born to women who had a severe infection during gestation.